Mathematical modeling of air coolers of indirect evaporative type - Chelabchi, Vladimir (Eastern-European Journal of Enterprise Technologies, 2017)
The method of integrated modeling of interconnected heat and mass transfer processes in air coolers of evaporative type has been developed. Air cooler of indirect evaporative type was taken as the object of research. Water was used as the evaporating agent. Basic schemes of airflows were considered: cross-flow and counter-flow. Partitioning of the problem into a number of subtasks (air flow distribution among channels, heat and mass transfer in the channel system) was proposed. Decomposition of the device structure into a number of elements was done. Mathematical models of interconnected processes of heat and mass transfer are given as a system of nonlinear ordinary differential equations in a one-dimensional statement. The developed efficient methods of joint solution of the mathematical model equations were used in simulation. A modified robust method for simulation of media flows in the channels of a complex profile (two-dimensional fields of velocity and temperature) was proposed. Joint solution of continuity equations, Navier-Stokes equation (in projections to the coordinate axes), Fourier equation and pressure equation was carried out. The method is invariant as to the channel shape and the properties of the working media. The method of calculation of heat exchange coefficients with the use of the obtained velocity and temperature fields is set forth. This enables to refine results of modeling of the processes proceeding in coolers. Computational and full-size experiments for a number of designs and operation conditions of air coolers were conducted. Comparative analysis of the obtained results has shown reliability of the proposed methods of mathematical modeling. Discrepancy between the calculated and experimental values of the cooled air temperature did not exceed 0.5 °C. The described method of mathematical modeling enables obtaining reliable information necessary to optimize the design and working conditions of coolers. The developed method of mathematical modeling of the heat and mass transfer processes can be used for a detailed study of various types of heat exchangers.